Protection of Personal Data Abuse in Online Lending in Indonesia - Sahrul Hanafi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
The misuse of personal data in online lending in Indonesia has become an important issue alongside the rapid growth of the digital finance sector. This study aims to analyze personal data protection in the context of online lending, focusing on Law No. 27 of 2022 and POJK No. 22 of 2023. The method used is a normative legal approach with a descriptive-analytical approach, which includes an analysis of legislation and data protection practices in the industry. The research subjects include both regulations and how they are applied in practice. Data collection techniques were conducted through document studies, including analysis of laws, regulations, and related literature. The main theory used is the theory of personal data protection, which emphasizes individual rights and the responsibilities of data controllers. The results of the study show that Law No. 27 of 2022 and POJK No. 22 of 2023 provide a comprehensive legal framework for personal data protection in online lending, with an emphasis on individual rights and the responsibilities of data controllers. Although this legal framework is already strong, there are still challenges in its implementation, so further efforts are needed to ensure effective personal data protection in this sector. The academic contribution of this research is to provide new insights into the effectiveness of regulations in protecting personal data and to encourage discussion on improving data protection implementation in the digital finance sector.Keywords: Personal Data Protection, Online Lending.